Memory and music in Mikhail Bulgakov's The Master and Margarita: Defying the regime - Nataliya Shpylova-Saeed (Logos et Littera: Interdisciplinary Approaches to Text, 2017)
Mikhail Bulgakov’s The Master and Margarita reveals intricate intersections, which are negotiated via memory and writing. Witnessing the collapse of the Russian Empire and the emergence of the Soviet Union, Bulgakov devises multiple ways to engage not only with political and historical changes but with literary and aesthetic changes as well. Known for its magical and phantasmagorical abundance, The Master and Margarita offers, in addition to a love story, a narrative that reveals the individual’s fragmented memory that is connected with existential uncertainty and lostness brought forth by political oppression. To illuminate the novel’s engagements with memory and existence, this essay brings attention to musical references that Bulgakov employs to produce multilayered narrative dimensions. Although music in Bulgakov’s novel has been mentioned on many occasions, this discussion shifts the emphasis from the writer’s love of music to the responses to the brutality of the Soviet regime and to the conflicts, arising from the state’s attempts to control the individual’s memory, private space. In this essay, memory and music are presented as means to defy the state’s dominance, control, and surveillance.